2020
DOI: 10.2147/opth.s267567
|View full text |Cite
|
Sign up to set email alerts
|

<p>Comparison Between the Effect of Femtosecond Laser in situ Keratomileusis (FS-LASIK) and Femtosecond Small Incision Lenticule Extraction (FS-SMILE) on the Corneal Endothelium</p>

Abstract: Purpose: To compare the effect of FS-LASIK and FS-SMILE on the corneal endothelial cell density (ECD) and morphology. Patients and Methods: This is a prospective, cohort observational study that included 80 eyes of two equal groups of patients. Forty eyes were subjected to the FS-LASIK, and 40 eyes were subjected to the FS-SMILE. In both groups, patients, age ranged between 19 and 37 years with myopia ranges from −0.75 to −9.00 diopters (D) and astigmatism up to −3.00D. The ECD, coefficient of variation (CV), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 17 publications
2
11
0
Order By: Relevance
“…These ndings suggest that endothelial cells may be trying to compensate for the decrease in ECD via polymegatism. Similar to our study, a recently published study by Shaaban et al [29] reported a statistically signi cant decrease in ECD and a change in endothelial morphology, although clinically insigni cant in both FS-LASIK and small incision lenticule extraction (SMILE). The effect on the endothelial cells may be related to the heat energy generated by the shock waves that occur when the ap is created with the FS laser.…”
Section: Discussionsupporting
confidence: 91%
“…These ndings suggest that endothelial cells may be trying to compensate for the decrease in ECD via polymegatism. Similar to our study, a recently published study by Shaaban et al [29] reported a statistically signi cant decrease in ECD and a change in endothelial morphology, although clinically insigni cant in both FS-LASIK and small incision lenticule extraction (SMILE). The effect on the endothelial cells may be related to the heat energy generated by the shock waves that occur when the ap is created with the FS laser.…”
Section: Discussionsupporting
confidence: 91%
“…Durrie et al [28] compared PRK with thin-flap LASIK and reported no significant changes in the ECD at the 3 rd postoperative month with both techniques and no difference between the two techniques. However, similar to us, a recently published study by Shaaban and Badran [29] reported a statistically significant decrease in ECD and a mild change in endothelial morphology, although clinically insignificant in both FS-LASIK and small incision lenticule extraction (SMILE).…”
Section: Discussionsupporting
confidence: 84%
“…Eleven studies focused on PRK only, one study focused on LASEK [ 22 ], one focused on Trans-PRK [ 23 ], two focused on LASIK or FemtoLASIK [ 24 , 25 ], and two analyzed SMILE [ 26 , 27 ]. Seven remaining studies were comparative trials, three studies focused on PRK and LASIK [ 28 , 29 , 30 ], one focused on PRK and LASEK [ 31 ], one focused on PRK and Epi-LASIK [ 32 ], one focused on LASIK and FemtoLASIK [ 33 ], and one analyzed FemtoLASIK and SMILE [ 34 ]. Five studies explored PRK or LASEK with an intraoperative 0.02% MMC application [ 22 , 23 , 32 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%